Multicultural Challenges in Educational Policies within a Non-Conservative Scenario: The Case of the Emerging Reforms in Higher Education in Brazil - Canen, Ana (Policy futures in education, 2005)
The article discusses the extent to which multiculturalism has had an impact in the emerging reforms in higher education in Brazil, against the backdrop of the rise of a new non-Conservative, Labour-oriented government whose political agenda is marked by a discursive stand against conservatism, neo-liberalism and neocolonialism. Building on a postcolonial critical multicultural approach and on the need to include ideology in discussions concerning educational reform, it argues that educational policies should work towards valuing cultural diversity and challenging discriminatory practices without falling into dichotomies that freeze subject and institutional identities and fail to consider their mobility, hybridization and contingency. It then proposes alternative perspectives to consider future policies in education that take multiculturalism on board in a transformational perspective.